2021
DOI: 10.1007/s43452-021-00304-5
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and mechanical properties of Titanium grade 23 produced by selective laser melting

Abstract: Selective laser melted Titanium grade 23 was characterized by low porosity, relatively large surface roughness and pronounced surface texture (i.e. surface grooves orientation). The band/layer microstructure was built of mixed α and β phases. The as printed structure exhibited very high compressive residual stresses with strong anisotropy (i.e., − 512 ± 17 MPa and − 282 ± 14 MPa along the laser scanning direction and along the transverse direction, respectively) and strong fiber crystallographic texture. The l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…Therefore, for the additive manufacturing of titanium, environmental control at different processing stages (powder handling, storage, 3D printing, de-binding, and sintering) is of critical requirement. Here, it is essential to mention that the amount of oxygen content in the specimens prepared by binder jetting is comparable with those made by selective laser melting (about 3000 ppm) [33]. Kazantseva et al [34] have shown that on the laser printed surface, the amount of oxygen and nitrogen can reach 3 wt.% and 0.05 wt.%, respectively.…”
Section: Mechanical Properties and Interstitial Impuritiesmentioning
confidence: 67%
See 1 more Smart Citation
“…Therefore, for the additive manufacturing of titanium, environmental control at different processing stages (powder handling, storage, 3D printing, de-binding, and sintering) is of critical requirement. Here, it is essential to mention that the amount of oxygen content in the specimens prepared by binder jetting is comparable with those made by selective laser melting (about 3000 ppm) [33]. Kazantseva et al [34] have shown that on the laser printed surface, the amount of oxygen and nitrogen can reach 3 wt.% and 0.05 wt.%, respectively.…”
Section: Mechanical Properties and Interstitial Impuritiesmentioning
confidence: 67%
“…The interstitials entrapped in the metal are responsible for increased tensile strength and reduced elongation. In contrast to annealed specimens after selective laser melting with a tensile strength of 1210 ± 50 MPa and tensile elongation of 3.9% [33], the mechanical properties of parts manufactured by binder jetting are closer to the commercial titanium alloy.…”
Section: Mechanical Properties and Interstitial Impuritiesmentioning
confidence: 86%
“…Therefore, for the additive manufacturing of titanium, environmental control at different processing stages (powder handling, storage, 3D printing, de-binding, and sintering) is of critical requirement. Here, it is essential to mention that the amount of oxygen content in the specimens prepared by binder jetting is comparable with those made by selective laser melting (about 3000 ppm) [33]. Kazantseva et al [34] have shown that on the laser printed surface, the amount of oxygen and nitrogen can reach 3 wt.% and 0.05 wt.%, respectively.…”
Section: Mechanical Properties and Interstitial Impuritiesmentioning
confidence: 68%
“…These distinctive attributes have rendered titanium highly coveted in various high-value sectors, notably in aerospace and related industries [3]. Within this class of alloys, Ti-6Al-4V extra low interstitial (ELI) stands out for its notable suppression of impurities, resulting in enhanced ductility and fracture toughness compared with the conventional Ti-6Al-4V [4,5]. Notably, it maintains resilience even at extremely low temperatures, rendering it indispensable in cryogenic applications.…”
Section: Introductionmentioning
confidence: 99%